Antecedents and anticipated outcomes of superstitious behavior among professional salespeople. Issue 3 (4th March 2014) - Mayo, Michael; Mallin, Michael
Abstract : Purpose: – The present study is a "first look" at sales superstitions with the purpose of establishing its prevalence among professional salespeople and examining the subsequent effects on sales person expected confidence, motivation, sales call behavioral intentions, and anticipated performance outcomes. Design/methodology/approach: – Data was collected from 234 industrial (business to business) salespeople. SmartPLS path modeling was used to test a model consisting of three antecedents and three outcomes of salesperson superstitious behavior intensity. Findings: – The findings reveal that salespeople are more likely to behave superstitiously when they believe in personal good luck and experience higher levels of role ambiguity. For these salespeople, outcomes such as expected increase in confidence and motivation, positive sales behavioral intentions, and performance outcomes were anticipated as a result of their superstitions. Research limitations/implications: – Social cognitive theory is used as an organizing framework to guide this review as well as to develop a model that describes the conditions that give rise to sales superstitions and its potential impact on expected sales confidence, motivation, call behavioral intentions, and anticipated performance outcomes. Originality/value: – Given the paucity of reports on sales superstitions, the present study extrapolates from other allied literatures to identify antecedents and consequences associated with engaging in superstitious behavior.